Uncertainty influence on AHP method ratings - Vinogradova, Irina (Lietuvos matematikos rinkinys, 2012)
The paper deals with the evaluation of the criteria impacting distance learning course content quality. The goal of the paper is to introduce the improved AHP method with Fuzzy triangle numbers used to determine the quality of distance learning courses. In the paper, the interval and discrete methods for weights determination are compared.
Keywords: distance learning course; AHP method; fuzzy number; evaluation of quality; group evaluation